Fatal venous thromboembolism associated with hospital admission: a cohort study to assess the impact of a national risk assessment target. Issue 23 (15th September 2013) - Lester, Will; Freemantle, Nick; Begaj, Irena; Ray, Daniel; Wood, John; Pagano, Domenico
Abstract : Objectives: In 2010, the Department of Health in England introduced an incentivised national target for National Health Service (NHS) hospitals aiming to increase the number of patients assessed for the risk of developing venous thromboembolism (VTE) associated with hospital admission. We assessed the impact of this initiative on VTE mortality and subsequent readmission with non-fatal VTE. Design: Observational cohort study. Patients: All patients admitted to NHS hospitals in England between July 2010 and March 2012. Interventions: An NHS hospital which assessed at least 90% of patient admissions achieved the quality standard. Main outcome measures: The principal outcome measured was death from VTE up till 90 days after hospital discharge using linked Office of National Statistics and Hospital Episode Statistics data. Results: In the principal analyses of patients admitted to hospital for more than 3 days, there was a statistically significant reduction in VTE deaths in hospitals achieving 90% VTE risk assessment: relative risk (RR) 0.85 (95% CI 0.75 to 0.96; p=0.011) for VTE as the primary cause of death. In supportive analyses of postdischarge deaths after index admissions of up to 3 days, there was also a reduction in fatal VTE RR 0.61 (0.48 to 0.79; p=0.0002). This effect was seen for both surgical and non-surgical patients. No effect was seen in day case admissions. There was no change in non-fatal VTE readmissions up to 90 days after discharge. Conclusions: A national quality initiative to increase the number of hospitalised patients assessed for risk of VTE has resulted in a reduction in VTE mortality.